Utilización de los materiales no estructurado y el logro de aprendizaje en el área de matemática en los niños de la I.E.I Cuna Jardin Nº 548 Mi Mundo Infantil, Iquitos 2022 - Nogueira Guzman, Cinthia Esther (2024)
The present study had the objective of relating the use of unstructured materials and the learning achievement in the area of mathematics in the children of the I.E.I Cuna Jardín Nº 548 mi mundo infantil Iquitos 2022, the relational methodology and non-experimental design. -Correlational, the sample was 152 5-year-old children, it was determined that 86.2% (n=131) children are at an optimal level in terms of the area of mathematics and 78.9% (n=120) always use unstructured materials, this demonstrates an ordinal relationship, when describing the level of use given to unstructured materials, 58.5% (n=135) constantly use these materials. When knowing the achievement in obtaining notion in the area of mathematics, 86.1% (n=131) of the children have achieved it. By associating both variables, the Pearson correlation test was applied, which yielded the result of rxy = 0.816 indicating the high positive association between the two variables. For the hypotheses proposed with the normality test, a bilateral significance of less than 0.05 was obtained, thus rejecting Ho and accepting Ha. The study hypothesis was demonstrated with Spearman's non-parametric Rho test, which showed rs=0.506*; Sig. < 0.05, it is concluded that the use of unstructured material is notably linked to the achievement of learning in the mathematical area in children I.E.I Cuna Jardín Nº 548 my children's world Iquitos 2022.